Interface traps at Al2O3/InAlN/GaN MOS-HEMT -on- 200 mm Si. (November 2017) - Kumar, Sandeep; Remesh, Nayana; Dolmanan, S.B.; Tripathy, S.; Raghavan, S.; Muralidharan, R.; Nath, Digbijoy N.
Abstract: We report on the characterization of the interfaces of Al2 O3 /InAlN/GaN HEMT structure grown on 200 mm diameter silicon using conductance dispersion technique. Irreversible threshold voltage (VTH ) shift of up to +∼2.5 V was observed due to the gate stress induced activation of acceptor states. Further, frequency dependent VTH shift during capacitance voltage measurements were also recorded due to the presence of slow traps at InAlN/GaN interface. The conductance dispersion indicated the presence of acceptor traps of the order of ∼4 × 10 12 to 7 × 10 13  cm −2  eV -1 with a time constant of ∼10 to 350 μs at the InAlN/GaN interface. Trap density at the Al2 O3 /InAlN was found to be in similar range but with a time constant of ∼2 µs. The presence of high density of traps at InAlN/GaN interface is attributed to the unavoidable growth interruption before the start of InAlN growth.